High-Frequency Spinal Cord Stimulation at 10 kHz for the Treatment of Combined Neck and Arm Pain: Results From a Prospective Multicenter Study. Issue 2 (3rd December 2019) - Amirdelfan, Kasra; Vallejo, Ricardo; Benyamin, Ramsin; Yu, Cong; Yang, Thomas; Bundschu, Richard; Yearwood, Thomas L; Sitzman, B Todd; Gliner, Bradford; Subbaroyan, Jeyakumar; Rotte, Anand; Caraway, David
Abstract: BACKGROUND: Intractable neck and upper limb pain has historically been challenging to treat with conventional spinal cord stimulation (SCS) being limited by obtaining effective paresthesia coverage. OBJECTIVE: To assess the safety and effectiveness of the 10-kHz SCS system, a paresthesia-independent therapy, in the treatment of neck and upper limb pain. METHODS: Subjects with chronic, intractable neck and/or upper limb pain of ≥5 cm (on a 0-10 cm visual analog scale [VAS]) were enrolled in 6 US centers following an investigational device exemption from the Food and Drug Administration (FDA) and institutional review board approval. Each subject was implanted with 2 epidural leads spanning C2-C6 vertebral bodies. Subjects with successful trial stimulation were implanted with a Senza® system (Nevro Corp) and included in the evaluation of the primary safety and effectiveness endpoints. RESULTS: In the per protocol population, the primary endpoint (≥50% pain relief at 3 mo) was achieved in 86.7% (n = 39/45) subjects. Compared to baseline, subjects reported a significant reduction ( P  < .001) in their mean (± standard error of the mean) VAS scores at 12-mo assessment for neck pain (7.6 ± 0.2 cm, n = 42 vs 1.5 ± 0.3 cm, n = 37) and upper limb pain (7.1 ± 0.3 cm, n = 24 vs 1.0 ± 0.2 cm, n = 20). At 12-mo assessment, 89.2% of subjects with neck pain and 95.0% with upper limb pain had ≥50% pain relief from baseline, 95.0% reported to be "satisfied/very satisfied" and 30.0% either eliminated or reduced their opioid intake. CONCLUSION: In conclusion, 10-kHz SCS can treat intractable neck and upper limb pain with stable long-term outcomes.